P169 Investigating the Impact of Social Deprivation in Lung Cancer Patients in North Glasgow. (19th November 2012) - Tweed, C; Farley, J; Horst, J Van Der; Bicknell, S; Maclay, J; Milroy, R
Abstract : Introduction: Lung cancer incidence and mortality rates are highest in the most deprived regions of Scotland. Glasgow has the highest incidence rate for lung cancer in Scotland at 92.8 people per 100, 000 population and the highest mortality rate at 75.4 people per 100, 000 population. The DEPCAT score is a well-validated index of deprivation unique to Scotland, based on post code. DEPCAT categorises deprivation into groups 1 (most affluent) to 7 (least affluent). We investigated social deprivation in North Glasgow and its relationship to lung cancer presentation, investigation, treatment, and mortality. Methods: All patients with lung cancer diagnosed in North Glasgow in 2009 and 2010 were prospectively recorded in a registry. We investigated prevalence, stage at presentation, performance status, attempts at tissue diagnosis and treatment administered with the DEPCAT score. Results: 1190 patients were diagnosed with lung cancer in the study period and clinical details were recorded at a multidisciplinary meeting. DEPCAT was available in more than 99% of patients. 61% of patients were from the most deprived categories (6 and 7). Lung cancer was more prevalent in deprived areas (Table 1 ). Stage at presentation was not different based on social deprivation, but patients from deprived areas had a poorer performance status at presentation (PS 0–1 DEPCAT1–2: 58% vs DEPCAT 6–7:40%). While there was no difference in whether tissue diagnosis was attempted, fewer patients from DEPCAT 6–7 underwent surgery or radical radiotherapy and more of this group were treated with best supportive care (Table 1 ). There was a trend to better median survival in more affluent groups, but confidence intervals were overlapping. Conclusions: We found that the prevalence of lung cancer was higher in more deprived areas, in keeping with previous studies, and that these patients had a worse performance status at diagnosis despite similar stage of disease at presentation. Although there was no difference in pursuit of tissue diagnosis, fewer patients from more deprived areas underwent curative treatment. These differences in lung cancer diagnosis and management could be attributable to higher rates of co-morbidity in areas of lower socio-economic class.